2016
DOI: 10.1177/0145482x1611000505
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Wearables and Youths with Visual Impairments: Implications for Practice and Application

Abstract: Introduction Individuals with visual impairments are at risk for chronic health-related illnesses attributed to low physical activity and low fitness levels. This study aimed to determine device preference of three physical activity–monitoring wearables for youths with visual impairments, taking into account gender and visual impairment level, and to discern beneficial and impeding device components and suggested device changes. Methods For this cross-sectional and descriptive study, a convenience sample of 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Those above 34 years of age are able to truly enjoy the smartwatches they bought for themselves. A gender difference was also documented in a study by Colgan, Bopp, Starkoff, and Lieberman (2016), who discovered that female students attend more to aesthetic aspects of the wearable devices (e.g., color and font face) and male students care more about functionality such as whether the device is waterproof. Similar to the 2016 Ericsson ConsumerLab study aforementioned, a dissatisfaction is also noted in a later report by Gartner (2016), an international IT research and advisory firm.…”
Section: Background and Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Those above 34 years of age are able to truly enjoy the smartwatches they bought for themselves. A gender difference was also documented in a study by Colgan, Bopp, Starkoff, and Lieberman (2016), who discovered that female students attend more to aesthetic aspects of the wearable devices (e.g., color and font face) and male students care more about functionality such as whether the device is waterproof. Similar to the 2016 Ericsson ConsumerLab study aforementioned, a dissatisfaction is also noted in a later report by Gartner (2016), an international IT research and advisory firm.…”
Section: Background and Introductionmentioning
confidence: 84%
“…Males are more likely to use the wearables for learning when compared with females even though there are, totally, more female students using the wearables for school according to this survey. It may well be that when responding to the survey questions on wearable technologies, students identified more with the devices' functionality than their aesthetic values as Colgan et al (2016) discovered. As implied earlier, the 2016 data also revealed that about one out of eight students (12.6%) uses some type of wearable devices in the classroom, which has doubled from the previous year.…”
Section: Discussionmentioning
confidence: 99%
“…Perusse et al 's (2016) research found that lower PEOU and PU decreased the acceptance rate of wearables. Other problems and barriers to the use of wearable technology include weakness/lack of durability (Paul et al 2014;Wang et al 2016a, b), discomfort (Bowman et al 2016), invasive monitoring (Coorevits and Coenen 2016), inaccuracy (Kim et al 2007;Preusse et al 2016); limited designs (Colgan et al 2016;Tomberg et al 2015;Wang et al 2016a, b), cost (Donkin 2016), uselessness (Donkin 2016;Motti and Caine 2016) and difficulty of use (Coorevits and Coenen 2016). Researchers have endeavored to develop durable products that can withstand frequent washing or long-term use through methods such as coating the surface of the conductive materials or applying nanotechnologies (Paul et al 2014;Wang et al 2016a, b).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…When designing technology for people with visual impairment (PVI), there has been a strong focus on the design of tools for navigation and wayfinding [2,44,60,63,76,82,85], for mobility training [122], and tools for creating, communicating and rendering graphical information [3,17,75], with less attention being placed on leisure activities such as creating art [52], travel [104], dating [65], participating in sport or physical activity [31,56,73], making music [30], and playing games.…”
Section: Introductionmentioning
confidence: 99%